Dentist Mothers' Attitudes, Challenges and Facilitators in the Oral Health Promotion of Their Young Children - Damla Akşit-Bıçak (MDPI AG, 2023)
Twice daily parental supervised brushing (PSB) is recommended for the effective oral hygiene of children with toothpaste including fluoride. This cross-sectional study aimed to identify dentist mothers' attitudes, challenges, and facilitators in the oral health promotion of their young children. An online questionnaire was prepared and distributed to dentists via e-mail with a link to the form. Of all the mothers, 46.50% started brushing their children's teeth after the eruption of the first primary teeth. Nearly 50% of the mothers thought that they should brush their children's teeth until at least the age of 7-8 years old. In terms of the main barriers to toothbrushing, 52.9% said children could fall asleep at home or in the car, while 27.5% of all mothers reported being tired as the main barrier to toothbrushing. Although dentist mothers have sufficient knowledge to promote oral and dental health, they do not always have ideal attitudes and behaviors and they may encounter various barriers regarding themselves and their children in practical applications. Providing oral care for young children goes beyond 'knowledge' and is sometimes 'challenging'; however, it could be 'possible' by developing and implementing the most appropriate solution strategies suitable for each unique family and child.